2017
DOI: 10.1111/cdev.12772
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Socialization in Neighborhood Contexts: Implications for Ethnic Attitude and Identity Development Among Mexican‐Origin Adolescents

Abstract: Neighborhood Latino ethnic concentration, above and beyond or in combination with mothers' and fathers' ethnic socialization, may have beneficial implications for minority adolescents' ethnic attitude and identity development. These hypotheses, along with two competing hypotheses, were tested prospectively (from x¯age = 12.79-15.83 years) in a sample of 733 Mexican-origin adolescents. Neighborhood ethnic concentration had beneficial implications for ethnic identity processes (i.e., ethnic exploration and perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(107 citation statements)
references
References 84 publications
4
101
2
Order By: Relevance
“…Supple et al, who had a data set with a restricted range of neighborhood Latino concentration, found no cross-sectional association between neighborhood Latino concentration and ethnic-racial identity exploration (Supple et al, 2006). Prior analyses of data used in the current study, however, found that neighborhood Latino concentration positively predicted Mexican-origin adolescents' ethnic identity exploration above mothers' or fathers' ethnic socialization (White, Knight, et al, 2018). That work, however, did not examine the effects of neighborhood concentrated poverty on ethnic-racial identity exploration; nor did it examine whether neighborhood ethnic concentration may have longer term implications for adaptive and maladaptive functioning via its impact on ethnic-racial identity exploration.…”
Section: The Mediating Roles Of Ethnic-racial Identity Exploration Dcontrasting
confidence: 62%
See 1 more Smart Citation
“…Supple et al, who had a data set with a restricted range of neighborhood Latino concentration, found no cross-sectional association between neighborhood Latino concentration and ethnic-racial identity exploration (Supple et al, 2006). Prior analyses of data used in the current study, however, found that neighborhood Latino concentration positively predicted Mexican-origin adolescents' ethnic identity exploration above mothers' or fathers' ethnic socialization (White, Knight, et al, 2018). That work, however, did not examine the effects of neighborhood concentrated poverty on ethnic-racial identity exploration; nor did it examine whether neighborhood ethnic concentration may have longer term implications for adaptive and maladaptive functioning via its impact on ethnic-racial identity exploration.…”
Section: The Mediating Roles Of Ethnic-racial Identity Exploration Dcontrasting
confidence: 62%
“…None of these studies, however, focused specifically on Latinos, Mexican-origin Latinos, or on discrimination from peers. Two prior longitudinal studies conducted with the current sample, showed that higher levels of neighborhood Latino concentration (White, Knight, et al, 2018) or increases in neighborhood Latino concentration (White et al, 2014) predicted lower levels of discrimination from peers. Neither of those studies, however, examined the hypothesized mediational associations with later developmental outcomes.…”
Section: The Mediating Roles Of Ethnic-racial Identity Exploration Dmentioning
confidence: 62%
“…The ethnic and mainstream social identities and the associated knowledge, behaviors and expectations, attitudes and beliefs, and values are acquired through the processes of acculturation and enculturation, and occur through normative developmental processes and socialization processes in the home and broader community Motti-Stefanidi, Berry, Chryssochoou, Sam, & Phinney, 2012;White, Knight, Jensen, & Gonzales, 2018;White, Zeiders, & Safa, in press). These processes unfold over time and throughout the life span among individuals who have been in the United States for several generations as well as those who have recently immigrated.…”
Section: Developmental and Contextual Framework Application: Influencmentioning
confidence: 99%
“…The majority of existing research is based on objective measures of settings. Objective measures are widely used and often referred to as concentration, density, or proportion of individuals from a particular ethnic/racial group (e.g., Brown, 2017;Syed, et al, 2007;White et al, 2017). These measures are "objective" because they are based on official records, such as census or register data, and provide a description of the setting in terms of relative representation of different groups.…”
Section: Dimension 1: Perspectivementioning
confidence: 99%
“…Greater heterogeneity at both classroom and schools levels are related to adolescent perceptions of greater safety and social satisfaction (Juvonen, et al, 2006), which may, in turn, have implications for the development of ERI by providing a safe space for exploration. Greater concentration of co-ethnics in the neighborhood is related to adolescent reports of lower peer Density 27 discrimination as well as greater ERI exploration (White et al, 2017). Indeed, it is important to theorize and address more specifically what is happening within these dimensions.…”
Section: Conclusion and The Future Of Density And Erimentioning
confidence: 99%